Disposisi Berpikir Kreatif Matematis Pada Siswa Sekolah Dasar - Erna Yayuk; Dyah Worowirastri Ekowati (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2022)
The purpose of this research is to find out the creative thinking disposition of elementary school students in mathematics based on their gender group. The research design used is a descriptive qualitative method. Based on the results of the study, it can be concluded that boys have a high mathematical creative thinking disposition and positive perceptions, boys and girls have the same high mathematical creative thinking disposition and moderate perception, in the category of moderate mathematical disposition and moderate perception, students fewer boys than girls. In male students, moderate mathematical creative thinking disposition and negative perceptions have more numbers than in female students. Furthermore, students who have a low creative thinking disposition and moderate perception are only boys. Students who have low mathematical creative thinking disposition and negative perceptions are only female students. The level of disposition and perception is very influential in the process of learning mathematics. Children who have a high mathematical creative thinking disposition and high perception certainly have a better enthusiasm for learning mathematics than other categories,